Role of Oscillations in Auditory Temporal Processing: A General Model for Temporal Processing of Sensory Information in the Brain? - Bahmer, Andreas; Gupta, Daya Shankar (Frontiers in Neuroscience, 2018)
We review the role of oscillations in the brain and in the auditory system showing that the ability of humans to distinguish changes in pitch can be explained as a precise analysis of temporal information in auditory signals by neural oscillations. The connections between auditory brain stem chopper neurons construct neural oscillators, which discharge spikes at various constant intervals that are integer multiples of 0.4 ms, contributing to the temporal processing of auditory cochlear output. This is subsequently spatially mapped in the inferior colliculus. Electrophysiological measurements of auditory chopper neurons in different species show oscillations with periods which are integer multiples of 0.4 ms. The constant intervals of 0.4 ms can be attributed to the smallest synaptic delay between interconnected simulated chopper neurons. We also note the patterns of similarities between microcircuits in the brain stem and other parts of the brain (e.g., the pallidum, reticular formation, locus coeruleus, oculomotor nuclei, limbic system, amygdala, hippocampus, basal ganglia and substantia nigra), dedicated to the processing of temporal information. Similarities in microcircuits across the brain reflect the importance of one of the key mechanisms in the information processing in the brain, namely the temporal coupling of different neural events via coincidence detection.